2014
DOI: 10.1254/jphs.14071sc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Quetiapine on Per1, Per2, and Bmal1 Clock Gene Expression in the Mouse Amygdala and Hippocampus

Abstract: Abstract. Circadian rhythms are related to various psychiatric disorders. Recently, antipsychotics, including quetiapine (QTP), have been accepted as potential therapeutic agents for the treatment of depression, but its mechanism remains poorly understood. In this study, we examined clock gene fluctuation patterns in QTP-treated mice. QTP significantly increased Per2 mRNA at ZT12 and Per1 and Per2 expression at ZT18 in the amygdala. There were significant differences between the control and QTP groups in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Whether this immune system response reflects hippocampal function requires further investigation. Some studies have investigated the relationship between the hippocampus and alterations in proinflammatory cytokines, circadian rhythms and psychiatric disorders such as depression [10,27]. …”
Section: Discussionmentioning
confidence: 99%
“…Whether this immune system response reflects hippocampal function requires further investigation. Some studies have investigated the relationship between the hippocampus and alterations in proinflammatory cytokines, circadian rhythms and psychiatric disorders such as depression [10,27]. …”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that quetiapine can alter clock genes expression in mice, elevating Per1, Per2 and Bmal1 mRNA expression, depending on the circadian time (Moriya, Tahara et al 2014).…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
“…It has also been reported that various in vitro cultures of peripheral tissues and cell lines exhibit circadian rhythms [ 2 ]. Circadian rhythms are entrained by environmental cycles, such as sunlight, food, and temperature, and by various drugs and chemicals [ 3 – 8 ].…”
Section: Introductionmentioning
confidence: 99%